A Kunitz-type peptide from Dendroaspis polylepis venom as a simultaneous inhibitor of serine and cysteine proteases - Kodama, Roberto Tadashi; Kuniyoshi, Alexandre Kazuo; da Silva, Cristiane Castilho Fernandes; Cajado-Carvalho, Daniela; Duzzi, Bruno; Mariano, Douglas Ceolin; Pimenta, Daniel C.; Borges, Rafael [UNESP]; da Silva, Wilmar Dias; Portaro, Fernanda Calheta Vieira (FapUNIFESP (SciELO), 2020)
Background: Proteases play an important role for the proper physiological functions of the most diverse organisms. When unregulated, they are associated with several pathologies. Therefore, proteases have become potential therapeutic targets regarding the search for inhibitors. Snake venoms are complex mixtures of molecules that can feature a variety of functions, including peptidase inhibition. Considering this, the present study reports the purification and characterization of a Kunitz-type peptide present in the Dendroaspis polylepis venom as a simultaneous inhibitor of elastase-1 and cathepsin L. Methods: The low molecular weight pool from D. polylepis venom was fractionated in reverse phase HPLC and all peaks were tested in fluorimetric assays. The selected fraction that presented inhibitory activity over both proteases was submitted to mass spectrometry analysis, and the obtained sequence was determined as a Kunitz-type serine protease inhibitor homolog dendrotoxin I. The molecular docking of the Kunitz peptide on the elastase was carried out in the program Z-DOCK, and the program RosettaDock was used to add hydrogens to the models, which were re-ranked using ZRANK program. Results: The fraction containing the Kunitz molecule presented similar inhibition of both elastase-1 and cathepsin L. This Kunitz-type peptide was characterized as an uncompetitive inhibitor for elastase-1, presenting an inhibition constant (Ki) of 8 μM. The docking analysis led us to synthesize two peptides: PEP1, which was substrate for both elastase-1 and cathepsin L, and PEP2, a 30-mer cyclic peptide, which showed to be a cathepsin L competitive inhibitor, with a Ki of 1.96 µM, and an elastase-1 substrate. Conclusion: This work describes a Kunitz-type peptide toxin presenting inhibitory potential over serine and cysteine proteases, and this could contribute to further understand the envenomation process by D. polylepis. In addition, the PEP2 inhibits the cathepsin L activity with a low inhibition constant.
Keywords: Cysteine peptidase; Dendroaspis polylepis venom; Inhibitor; Kunitz-type peptide; Serine peptidase